Komunikasi Politik Masyarakat Pesisir Pedesaan di Kabupaten Konawe Kepulauan pada Pemilihan Umum dan Pemilihan Kepala Daerah Tahun 2024 - Sultrayansa; Rita Ayu Ningtyas (CV. ITTC INDONESIA, 2025)
This research discusses in detail the political communication that occurs in coastal and rural communities that have their own characteristics, the purpose of this research is to find out how political communication in rural coastal communities in Konawe Islands Regency using qualitative data analysis and data collection based on observation, interviews and document studies. The results of the study found that political communication in coastal and rural communities is strongly influenced by aspects of knowledge that shape people's perceptions and attitudes in conducting political communication. In particular, the level of knowledge of applicable regulations, as well as legislative and executive candidates form ways of communication that are more oriented towards values, morals that become the standard of society in conducting communication. Knowledge and emotional closeness to prospective leaders form a pattern of communication that is familial and humanist, so that even though the level of knowledge of the rules is not sufficient, the community still wants the contestation of elections and regional elections to take place in an atmosphere of kinship and mutual respect.